Dating and dragons - Boyce, Kristy (Delacorte Romance, 2024)
After starting at a new school, high school junior Quinn joins a D&D group to make friends but finds herself torn between her feelings for a charming yet annoying teammate and the drama stirred up by ex-friends from a previous campaign.